THE EFFECT OF SELF-EFFICACY ON GEOGRAPHY LEARNING OUTCOMES OF STUDENTS OF CLASS X IIS SMA NEGERI 1 TANGGETADA IN THE COVID-19 PANDEMIC - Luluh Inda Sari; Samsi Awal; Eko Hariyadi (USN Kolaka, 2021)
Study this aim for knowing influence self-efficacy to results study geography student Class X during the COVID-19 Pandemic. The research type is Ex-post facto. Population and sample study this consist from whole student class X IIS SMA Negeri 1 Tanggetada. Instruments used that is in the form of questionnaire self-efficacy consisting of 34 statements, documentation used for see results study geography student class X IIS. The analysis used in the research is descriptive and inferential. Research results are self-efficacy student Class X IIS SMA Negeri 1 Tanggetada during the COVID-19 Pandemic including in category medium, with students belonging to the category currently totaling 45 students or 50% of sample research. For result data study geography student class X IIS SMA Negeri 1 Tanggetada including in category medium, with students belonging to the category currently totaling 37 people or 42% of sample research. There is influence significant positive self-efficacy student to results study geography student class X IIS SMA Negeri 1 Tanggetada during the COVID- 19 pandemic 2021/2022 lesson, coefficient determinant (r 2 ) of 0.497 or 49.7% which means that the independent variable of self-efficacy has an influence of 49.7% on the learning outcomes of geography. It shows that self-efficacy students give contribution positive or good support in increase results study geography students.